Rancangan Dan Implementasi Virtual Tour 360 Berbasis Realitas Virtual Untuk Pemandu Kampus Digital (Studi Kasus : Universitas Hindu Indonesia) - I Putu Indrayana Putra; I Kadek Andy Asmarajaya; I Putu Mahendra Adi Wardana (Program Studi Sistem Informasi, Fakultas Teknologi Informasi dan Sains, Universitas Hindu Indonesia, 2026)
The advancement of information technology encourages higher education institutions to adopt interactive and immersive digital promotional media. The Indonesian Hindu University does not yet have a Virtual Reality-based platform capable of providing a comprehensive visualization of its campus environment. This study aims to design and implement a 360° Virtual Tour application as a digital campus guide using the Multimedia Development Life Cycle (MDLC) method, which consists of concept, design, material collecting, assembly, testing, anddistribution stages. The application was developed as a web-based system using 3DVista and PTGui software to generate interactive 360° panoramas. System testing was conducted through alpha testing by media experts using the Guttman scale, resulting in a 100% validation score, indicating that the application is highly valid. Beta testing involving 20 respondents using a Likert scale showed a feasibilityscore of 85.4%, categorized as highly feasible. The results indicate that the application provides an interactive and informative experience and is effective as a digital campus promotion and guidance tool